The Interrelationship Between Financial and Energy Markets - Ramos, Sofia.; Ramos, Sofia.; Veiga, Helena.; Veiga, Helena. (Lecture Notes in Energy, 2014)
In the last decade, energy markets have developed substantially due to the growing activity of financial investors. One consequence of this massive presence of investors is a stronger link between the hitherto segmented energy and financial markets. This book addresses some of the recent developments in the interrelationship between financial and energy markets. It aims to further the understanding of the rich interplay between financial and energy markets by presenting several empirical studies that illustrate and discuss some of the main issues on this agenda.